Impact of Military Expenditure on Economic Growth Encouraging or Constraining? - Nugroho, Dirga Ardian; Purwanti, Evi Yulia (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
Security is a form of guarantee that needs to be given by the state to its citizens. This fulfillment can be realized through the provision of national defense for all citizens. Nevertheless, military expenditure as a source of providing national defense needs attention. This is caused by its unproductive nature when compared to other sectors such as agriculture, banking, industry, and others. This study aims to analyze the effect of Military Expenditures on the level of Economic Growth. Furthermore, this study also analyzes the effect of interactions between Military Expenditure with other variables such as Population, Foreign Direct Investment (FDI), Political Stability, and Rule of Law, to see their indirect effects on Economic Growth. This study uses secondary data and covering 27 selected Lower-Middle Income Countries from 2002-2018. Furthermore, this study uses dynamic panel data analysis with the System Generalized Method of Moments (GMM) method. The Military Expenditure in this study does not significantly influence Economic Growth. However, it was found that Military Expenditure had a positive and significant influence on Economic Growth when interacting with other variables.